2019
DOI: 10.1101/2019.12.22.886606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skip segment Hirschsprung disease: modelling the trans-mesenteric origin of the enteric nervous system in the human colon

Abstract: Skip segment Hirschsprung disease is a difficult to explain human enteric neuropathy where a ganglionated region lies within a region of total colonic aganglionosis.. Recently, trans-mesenteric migration was described in the mouse intestine whereby neural crest cells migrate via the mesentery across a U-shape gut loop from the midgut to the hindgut: this could explain skip segment Hirschsprung disease. To investigate this, human intestinal growth parameters were derived from published sources and correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Moreover, based on the developmental anatomy of human intestine, recent work has implicated that transmesenteric migration is unlikely to occur in normal human embryogenesis. 70 The main difference between our model and the tmNCC model lies in the hypothesized origin of the NCCs within the gut mesentery. Based on the location of mNCCs within the gut mesentery, Nishiyama et al 35 preliminarily concluded that tmNCCs were derived from midgut eNCCs.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, based on the developmental anatomy of human intestine, recent work has implicated that transmesenteric migration is unlikely to occur in normal human embryogenesis. 70 The main difference between our model and the tmNCC model lies in the hypothesized origin of the NCCs within the gut mesentery. Based on the location of mNCCs within the gut mesentery, Nishiyama et al 35 preliminarily concluded that tmNCCs were derived from midgut eNCCs.…”
Section: Discussionmentioning
confidence: 95%